Role of new antibiotics for KPC-producing Klebsiella pneumoniae. (27th January 2021) - Theuretzbacher, Ursula; Carrara, Elena; Conti, Michela; Tacconelli, Evelina
Abstract: Klebsiella pneumoniae has accumulated a wide range of resistance determinants and has evolved into a difficult-to-treat pathogen that poses an increasing healthcare threat. KPC is an important marker for extensively drug-resistant (XDR) organisms with limited treatment options. In response to the medical need for new treatment options, several new antibiotics have been developed and registered recently. The β-lactamase inhibitor (BLI) combinations ceftazidime/avibactam, meropenem/vaborbactam and imipenem/relebactam, the cephalosporin–siderophore conjugate cefiderocol, the aminoglycoside derivative plazomicin and the tetracycline derivative eravacycline, focus on carbapenem-resistant Enterobacterales. These modified agents from old antibiotic classes illustrate the challenges of this requirement to address class-specific resistance mechanisms while critical gaps and some cross-resistance within a class, or to unrelated antibiotic classes, remain. The diverse molecular mechanisms and increasing diversification of carbapenem resistance among Klebsiella isolates requires improved rapid molecular diagnostic capabilities and stringent stewardship programmes to preserve the efficacy of new antibiotics for as long as possible.